Implementasi Sistem Management dalam Mengalami Pemborosan pada Lini Teknologi Informasi PT. Harrasima Inventory Logistic - Ali Ikhwan; Muhammad Daffa Fahreza; Eri Fahri Situmorang; Rahmat Pasaribu (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2025)
Organizations must keep boosting their operational efficiency in the age of globalization and fiercer commercial competition if they want to be competitive and provide customers more value. In the technology industry, PT Harrasima Inventory Logistic is a company that distributes rental items. PT Harrasima Inventory Logistic's human resource management is subpar, according to the findings of observers. According to the author, bureaucracy can use management information systems to enhance decision-making, organizational performance, rapid information dissemination, and other operational tasks.